The Influence of Marketing Stimuli on Consumer Purchase Decision of Malaysia’s Cosmetic Industry - Khalilah Abd Hafiz; Khairul Anuar Mohd Ali (International Journal of Supply Chain Management, 2018)
Cosmetics play essential roles and have animpactonconsumers everyday lives on building one self-esteem and confidence. Young consumers have become beauty conscious and engaging in the beauty lifestyle. Demand for cosmetics is dynamic in Malaysia, however, less attention dedicated to the cosmetic industry in the local setting in the literature. One main issue faced by marketers is their changing behaviour, tastes, and preferences. Marketers have the challenges in trying to cope with their behavioural changes and understanding their decision-making factors and processes correctly and accurately. Hence, the paper aims to examine the influence of product, price, promotion, and place on consumer purchase decision of makeups. The researchers applied store intercept model (convenience sampling) by using self-administered survey. Multiple regression was employed. The researchers conducted a pilot study of 102 respondents aged from 18 to 25 years old who shopped at shopping malls in Klang Valley, Malaysia. The empirical results confirm that promotion is the only construct that has a significant relationship with consumer purchase decision.